Ethnic Identity and Coping Strategies as Moderators of COVID-19 Racial Discrimination Experiences Among Chinese Americans. (3rd July 2022) - Litam, Stacey Diane Arañez; Oh, Seungbin
Abstract: A moderated mediation path analysis indicated COVID-19 racial discrimination was negatively associated with life satisfaction and positively related to depression in Chinese immigrants and Chinese Americans (CCA; N = 187). Strong ethnic identity moderated the relationship between COVID-19 discrimination and depression. Higher levels of coping moderated the relationship between depression and life satisfaction. Professional counselors are thus called to help CCA clients expand their coping skills to mitigate the effects of pandemic-related discrimination. Counselors can also help Chinese clients raise their critical consciousness and understand how oppressive systems and experiences of discrimination are linked to overall mental health and wellbeing.